Cerebrovascular burden and neurodegeneration linked to 15-year odor identification decline in older adults - Oltra, Javier; Kalpouzos, Grégoria; Ekström, Ingrid; Larsson, Maria; Li, Yuanjing; Qiu, Chengxuan; Laukka, Erika J. (Frontiers in Aging Neuroscience, 2025)
BackgroundThe mechanisms underlying olfactory decline in aging need further investigation. Noticeably, the longitudinal relationship of biological markers with olfaction remains underexplored. We investigated whether baseline levels and progression of microvascular lesions and brain atrophy are associated with odor identification (OID) decline.MethodsThe association between structural MRI markers and OID decline was examined in participants from the SNAC-K MRI study who were free from dementia at baseline (n = 401, mean age = 70.2 years, 60% females). OID was repeatedly assessed over 15 years. Presence of lacunes, white matter hyperintensities (WMH), perivascular spaces (PVS), and lateral ventricular, hippocampal, amygdalar, and total gray matter (GM) volumes were assessed up to 6 years, concurrent with the first 6 years of olfactory assessments.ResultsHigher PVS count and lower hippocampal and GM volumes at baseline were associated with accelerated OID decline (pFWE < 0.05). Longitudinally (n = 225), presence of lacunes at follow-up, faster WMH volume and PVS count increases, faster lateral ventricular enlargement, and faster hippocampal, amygdalar, and GM atrophy were associated with accelerated OID decline (pFWE < 0.05).ConclusionOlfactory decline is related to both increased cerebrovascular burden and accelerated brain atrophy over time.